Pengembangan Paham Moderasi Beragama di Pondok Pesantren Al-Ikhlas Ujung Kabupaten Bone - Arake, Lukman; Makkarateng, Ma'adul Yaqien (Atta'dib Jurnal Pendidikan Agama Islam, 2023)
Moderate attitudes in understanding and practicing religious teachings are highly necessary to be instilled in every Muslim, as they lead to the avoidance of conflicts with people from different beliefs. Islamic teachings about moderation in worship, as written in the Qur'an and Hadith, imply the principles of justice and balance in practicing religion. These principles are the essence of Islamic teachings that emphasize the "wasathiyah" or moderate approach in adhering to religious doctrines. Providing an understanding of religious moderation must be integrated into the curriculum of an Educational Institution. Hence, this research focuses on Islamic boarding schools (pondok pesantren) as the target of the study, as they are one of the Religious Educational Institutions in Indonesia. By employing the Community Based Research method and using a quantitative approach in data analysis, this study concludes that the development of the understanding of religious moderation in Pondok Pesantren Al-Ikhlas Ujung, Bone Regency, has shown improvement. The researcher's efforts in this development involved conducting seminars/dialogues and distributing books containing speeches related to the theme of religious moderation.Keywords : Religious Moderation, Islamic Boarding School, Tolerance, Anti-Violence